2011
DOI: 10.1017/s0007485311000423
|View full text |Cite
|
Sign up to set email alerts
|

Wing shape as a potential discriminator of morphologically similar pest taxa within theBactrocera dorsalisspecies complex (Diptera: Tephritidae)

Abstract: Four morphologically cryptic species of the Bactrocera dorsalis fruit fly complex (B. dorsalis s.s., B. papayae, B. carambolae and B. philippinensis) are serious agricultural pests. As they are difficult to diagnose using traditional taxonomic techniques, we examined the potential for geometric morphometric analysis of wing size and shape to discriminate between them. Fifteen wing landmarks generated size and shape data for 245 specimens for subsequent comparisons among three geographically distinct samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 39 publications
1
79
0
3
Order By: Relevance
“…For this reason, several studies have been conducted to clarify the taxonomic puzzles, for example on taxonomy, molecular genetics, behaviour, chemical and cytogenetic reactions (Tan et al 2011;Khamis et al 2012;Schutze, Jessup, et al 2012Boykin et al 2013;Krosch et al 2013;Schutze et al 2013;Tan et al 2013). Despite the difficulties, several discoveries have been made at a basic level on its taxonomic situation via the implementation of the tools that have been discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, several studies have been conducted to clarify the taxonomic puzzles, for example on taxonomy, molecular genetics, behaviour, chemical and cytogenetic reactions (Tan et al 2011;Khamis et al 2012;Schutze, Jessup, et al 2012Boykin et al 2013;Krosch et al 2013;Schutze et al 2013;Tan et al 2013). Despite the difficulties, several discoveries have been made at a basic level on its taxonomic situation via the implementation of the tools that have been discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that the differences were determined to be in the volatile components of male reproductive organs (Wee & Tan 2005). Furthermore, the wing shape in geometric morphometric analysis (Schutze, Jessup, et al 2012) and the morphometry of the male aedeagus (Iwahashi 2001) have been useful in discerning members of the B. dorsalis species complex. The time divergence estimated from the fossil record of the Tephritidae family also showed that the well-resolved B. dorsalis species complex with all members shares a common ancestor at 6 million years ago (MYA) (in the Pliocene period) .…”
Section: Introductionmentioning
confidence: 99%
“…Orientation (or rotation) and scale effects attributed to each specimen are removed during analysis [43], and subtle sources of variation that are not easily summarized by simple linear measurements are more completely captured [42,[44][45][46]. Although landmark-based morphometric analyses have been widely used to investigate the relationships between form and function in insects [47], the sole previous study in birds investigated only six closely related species [46]. So far to our knowledge, no landmark-based morphometric analysis has been used to investigate broader patterns of variation in wing shape across Aves.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen homologous type I landmarks (Bookstein 1997) consisting of points at which a wing vein meets the edge of the wing, or wing vein and cross-vein intersections were selected. Thirteen of the landmarks were homologous to those of Schutze et al (2011), and an additional four were chosen to try to obtain a higher resolution of species and of genotypic clusters. No landmarks were chosen in the anterior and posterior regions of the wing because these areas are most easily damaged.…”
Section: Methodsmentioning
confidence: 99%